2021
DOI: 10.3390/ijms22052525
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Myelodysplastic Syndromes: A Challenge for Adult Hematologists

Abstract: Myelodysplastic syndromes (MDS) arising in the context of inherited bone marrow failure syndromes (IBMFS) differ in terms of prognosis and treatment strategy compared to MDS occurring in the adult population without an inherited genetic predisposition. The main molecular pathways affected in IBMFS involve telomere maintenance, DNA repair, biogenesis of ribosomes, control of proliferation and others. The increased knowledge on the genes involved in MDS pathogenesis and the wider availability of molecular diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Interestingly, the aetiology of the inherited MDS is associated with germline predisposition in genes involved in telomere maintenance, DNA repair, biogenesis of ribosomes and cell proliferation. Further detailed reviews on the genetics and clinical implications of various gene mutations in these disorders have been extensively covered elsewhere [7][8][9][10]. Recent studies have suggested that the addition of molecular data to the prognostic scoring systems can improve its predictive applicability in the clinical settings [6,[11][12][13], that will not only help in the clinical diagnosis but can also be used for the monitoring of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the aetiology of the inherited MDS is associated with germline predisposition in genes involved in telomere maintenance, DNA repair, biogenesis of ribosomes and cell proliferation. Further detailed reviews on the genetics and clinical implications of various gene mutations in these disorders have been extensively covered elsewhere [7][8][9][10]. Recent studies have suggested that the addition of molecular data to the prognostic scoring systems can improve its predictive applicability in the clinical settings [6,[11][12][13], that will not only help in the clinical diagnosis but can also be used for the monitoring of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that certain germline variants predispose to the development of CH. Genetic carriers of telomere biology disorders have an increased risk of developing both interstitial lung disease and CH carrying DDR gene variants (29). To test the hypothesis that germline variants in genes predisposing in telomere maintenance genes are enriched in lung transplant patients with DDR CH, we performed whole exome sequencing on a subset of 52 patients, including all patients with ILD or DDR CH.…”
Section: Germline Predisposition To Idiopathic Pulmonary Fibrosis and Chmentioning
confidence: 99%